Teachers’ Developmental Roles in Local Wisdom-Based Character Education Across Learning Phases: A Phenomenological Study at Primary School - Marina Luksiana Azhan; Fuji Afriani; Anggianita Putri Wulandari; Suherli Kusmana (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
Local wisdom-based character education plays a vital role in strengthening students' cultural identity and character development. However, studies examining teachers' roles in implementing local wisdom-based character education across different developmental phases remain limited, particularly within the cultural context of Cirebon, Indonesia. This study aimed to analyze teachers' roles, instructional strategies, and implementation challenges across Phases A, B, and C while developing an implementation framework for local wisdom-based character education. A qualitative phenomenological approach was employed involving three purposively selected teachers representing Phases A, B, and C at SDN 1 Kedawung. Data were collected through semi-structured interviews and documentation. Data analysis followed phenomenological procedures involving bracketing, identification of meaning units, thematic clustering, and synthesis of participants' lived experiences, supported by the interactive analysis model of Miles, Huberman, and Saldaña. Trustworthiness was ensured through triangulation, member checking, and researcher reflexivity. The findings revealed that teachers adapted their roles and instructional strategies to students' developmental characteristics across learning phases. Local wisdom-based activities, including Cirebon mask dance, batik-making, educational visits to the Kesepuhan Palace, and regional culinary projects, fostered discipline, responsibility, cooperation, creativity, cultural appreciation, and self-confidence. This study proposes a six-stage implementation framework integrating teacher roles, developmentally appropriate instructional strategies, local wisdom, and character outcomes, providing a practical model for implementing contextually relevant character education in elementary schools.